2021
DOI: 10.1109/access.2021.3101716
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Recognition of Human-Object Interactions via Gaussian-Based Elliptical Modeling and Pixel-Level Labeling

Abstract: Human-Object Interaction (HOI) recognition, due to its significance in many computer visionbased applications, requires in-depth and meaningful details from image sequences. Incorporating semantics in scene understanding has led to a deep understanding of human-centric actions. Therefore, in this research work, we propose a semantic HOI recognition system based on multi-vision sensors. In the proposed system, the de-noised RGB and depth images, via Bilateral Filtering (BLF), are segmented into multiple cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Random fields is the general form of stochastic process where we don’t need the real values and it can take multi-dimensional matrix or points Khalid et al (2021) . Hence, we applied it over multi-dimensional signals like motion and physiological signals together.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Random fields is the general form of stochastic process where we don’t need the real values and it can take multi-dimensional matrix or points Khalid et al (2021) . Hence, we applied it over multi-dimensional signals like motion and physiological signals together.…”
Section: Methodsmentioning
confidence: 99%
“…Next, to decide the kinematic-static patterns among the windows ( Al Shloul et al, 2022 ), we suggested a polynomial probability distribution. For kinematic patterned signal data, multisynchrosqueezing transform ( Yu, Wang & Zhao, 2019 ) and hidden Markov random field ( Wang, 2012 ) are suggested for features extraction, whereas, for static patterned signal windows, dynamic time warping ( Laperre, Amaya & Lapenta, 2020 ) and Gaussian Markov random field ( Khalid et al, 2021 ) are recommended. Then, two feature optimization techniques are used including quadratic discriminant analysis and orthogonal fuzzy neighborhood discriminant analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the convolutional neural networks (ConvNets) and Polynormal fisher vector was used for classification. Another system [16] denoised depth images through Bilateral Filter (BLF) and segmented image clusters using Simple Linear Iterative Clustering (SLIC) algorithm. The actions were then classified using K-ary Tree Hashing (KTH).…”
Section: Action Recognition Via Video Sensormentioning
confidence: 99%
“…Domestic researchers mainly focus on the comparison of women's volleyball team's offensive ability with their opponents in different world competitions, especially statistics on offensive indicators such as serving, passing, and attacking. It is one of the important standards of the world's strong teams, and the women's volleyball team needs to strengthen the training of the stability of the attack and smash [9,10].…”
Section: Introductionmentioning
confidence: 99%